Miscellanea Neo-sumerica I-III - Owen, David I. (Fs Gordon)
copies; CBS 9766 and Ur-dNanibgal(a), ensi of Nippur; UM 29-13-268, Mar-du8 supports reading Mar-dú(= Tu); UNC 7 (photo pl. II*), a campaign against Mardu in the third year of Ibbī-Sîn.